White gold - International Center for Tropical Agriculture (2015)
Despite substantial investments in crop breeding, bottlenecks in accessing quality bean seed in Africa persist. But recent successes show how the bottlenecks can be broken, and the challenge now is to scale up successful approaches with bean seed systems more rapidly. The International Center for Tropical Agriculture (CIAT), National Bean Research Programs through the Pan-African Bean Research Alliance (PABRA) and the Syngenta Foundation for Sustainable Agriculture (SFSA) are working together and with other partners to meet the challenge.